Keterlekatan Tindakan Ekonomi Pedagang Keliling (Studi Kasus di Desa Melati Kecamatan Waringinkurung Kabupaten Serang) - Nasiroh, Nasiroh; Haryono, Haryono; Afrizal, Stevany (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
This research discusses the embeddedness of actors in carrying out economic actions and describes the social situation carried out by traveling traders in Melati Village. The study was conducted on economic actors in Melati Village, Waringinkurung District, Serang Regency. The aim of this research is to analyze the embeddedness between actors in carrying out economic actions and describe the social situations that occur when actors carry out economic activities in their daily lives. The form of embeddedness that exists between actors in carrying out economic actions is relational embeddedness. This is based on a sense of trust and values that are personally attached and have been around for a long time which are expressed in the form of action. There is a sense of trust between traders and buyers which leads to strong attachment and weak attachment. So the focus of this research is to look at the embeddedness between traveling traders so that a network or group of traveling traders is formed. This research uses a descriptive qualitative method with a case study approach. Meanwhile, the data analysis techniques used are data collection, data reduction, data presentation and drawing conclusions. The results of this research show that there is attachment in a relational form which is based on a sense of trust and long-lasting interpersonal values. The existence of a sense of trust and mutual need between traders and buyers can be a complement in carrying out economic actions. This is related to the patterns of social interaction that develop between actors creating inherent economic actions that are influenced not only by economic aspects but also by social and cultural aspects.